View Single Post
Apr23-10, 12:44 AM
HW Helper
P: 6,202
Converting square root to perfect square

Quote Quote by cstvlr View Post
no its in an equation form,

C(x) = [(9-x) + 1.25sqrt( x^2 + 36 )], where C(x) is a function.

and they're trying to solve for x, so they used the method above, and I know how to solve it, but I lost it when they used let x = 3( t - 1/t )
x = 3( t - 1/t ) ⇒ x2 = 9( t - 1/t )2

∴√(36+x2)=√(36+9(t- 1/t)2), how does that turn into an expression like √(a+b)2?

I do not think there rule per se for using that substitution though.